1997
DOI: 10.1034/j.1399-3054.1997.990406.x
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and regeneration of transgenic aspen plants via shoot formation from stem explants

Abstract: 1997. Transformation and regeneration of transgenic aspen plants via shoot formation from stem explants. -Physiol. Plant. 99: 554-561.An Agrobacterium-mtdmted transformation procedure for aspen (Populus tremula L.), involving the direct regeneration of shoot-buds from stem explants, is described. Disarmed Agrobacterium tumefaciens strain EHAlOl harboring the binary plasmid pKIWI105 (which carries the uidA and n pi 11 gen&s, coding for/?-glucuronidase [GUS] and neomycin phosphotransferase II, respectively) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Several transformants were selected for further analysis, and all of them showed kanamycin resistance as reflected by the high ability of rooting in the presence of kanamycin. Similar results were reported by TZFIRA et al (1997). The transgenic origin of the plants obtained during this study will be confirmed by PCR analyses.…”
Section: Transformationsupporting
confidence: 77%
“…Several transformants were selected for further analysis, and all of them showed kanamycin resistance as reflected by the high ability of rooting in the presence of kanamycin. Similar results were reported by TZFIRA et al (1997). The transgenic origin of the plants obtained during this study will be confirmed by PCR analyses.…”
Section: Transformationsupporting
confidence: 77%
“…IBA was used to induce roots for leaf of aspen and zeatin was used for shoot regeneration [24]. Adventitious shoots regenerated in a woody plant medium (WPM) supplemented with TDZ (Thidiazuron) from aspen stem explants [16]. Ferreira et al [14] reported that adventitious shoot regeneration of P. euphratica from organogenic nodules of leaf explants was achieved within a range of concentrations of a-naphtalenacetic acid and 6-benzylaminopurine, at a fixed 2:1 ratio.…”
Section: Resultsmentioning
confidence: 99%
“…Growth and differentiation response is not only controlled by the cultural environment, but is also dependent upon the genotype [11]. In vitro regeneration has been attempted in several poplar species using different explants such as leaves [8,11–14], petioles [15], internodes [8,14], stems [5,16], roots [8,11], and shoot tips [17]. The leaf disc transformation method [18] has been widely used in plant genetic engineering.…”
Section: Introductionmentioning
confidence: 99%